Myocarditis after COVID-19: Comparing risks from vaccination and infection - Bari, Anass; Bari, Jawad (Journal of the Pakistan Medical Association, 2026)
Respected Editor, An inflammation of the heart muscle is called myocarditis. COVID-19 mRNA vaccine related myocarditis has drawn a considerable amount of attention in public. Fear of complications post-vaccination is a key obstacle in vaccine uptake. Therefore, it is crucial to put these concerns to contextualiseof extensive clinical data. A meta-analysis by Voleti et al reported that relative risk of getting myocarditis in patients with covid-19 related infection was seven times more than the group with mRNA covid vaccines1. The U.S. food and drug administration in their 2025 updated reported that myocarditis was reported to be approximately eight cases per million doses in individuals aged 6 months to 64 years and the number rose to 27 per million doses in males aged 12 to 24 years2. A study conducted from March 2020 to January 2021 reported that the risk of getting myocarditis in covid-19 patients was 16 times higher than those without infection3. A study by Shay et al (2021) reported that myocarditis associated with vaccine typically presented as mild, was rarely associated with deaths, and was responsive to non-steroidal anti-inflammatory drugs (NSAIDs) 4. Patone et al (2022) reported contrasting presentation of myocarditis associated with covid-19 infection, this type of infection more frequently led to ventricular dysfunction, arrhythmias and fatalities5. Semenzato et al (2024) conducted a countrywide cohort study in France which reported less severe cardiovascular events after 18 months of follow up in post-vaccinationmyocarditis compared to myocarditis of other origins6. The disparity in incidence and outcomes severity strongly suggest that the benefits of COVID-19 mRNA vaccine outweigh the risks. Considering these findings, we recommend that the public should be informed regarding the risks of COVID-19 infection related myocarditis, which poses a greater threat as compared to COVID-19 mRNA vaccine associated myocarditis. We recommend that high risk groups should be identified, and alternate formulations or dosing intervals should be used for the high-risk group. More extensive randomised trials and continuous monitoring of vaccinated people should continue to refine our understanding of vaccine and infection related complications.